The specific features of arthropathy in Whipple's disease - I V Maev; E V Zhilyaev; D T Dicheva; T A Buragina; E G Prokhorova; I V Mayev; E V Zhilyaev; D T Dicheva; T A Buragina; E G Prokhorova (Современная ревматология, 2008)
The authors describe a case of Whipple's disease (WD) in a 56-year-old male patient followed up for 2 years. The diagnosis was established on the evidence that there was a low-density retroperitoneal or mesenteric infiltrate at computed tomography and PAS-positive macrophages in the biopsy specimens of the duodenal retrobulbar mucosa. Arthropathy had developed within 10 years before the occurrence of intestinal symptoms, subsided with their progression, and recurred after their regression. On the basis of this observation and the data available in the literature, the authors discuss the relationships of arthropathy to the abdominal manifestations of WD.